Strategi Kepala Sekolah dalam Meningkatkan Kinerja Guru pada Masa Pandemi Covid-19 di SMP Negeri 10 Binjai - Al Fajri Bahri; Mhd. Fazlur Rahman; Rizka Nur; Mishiyyah Nashih Ulwan; Agil Syahputra; Fachruddin Azmi; Amiruddin Amiruddin (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
Currently, countries around the world, including Indonesia, are still experiencing the Covid-19 pandemic. One of the consequences is in the field of education where face-to-face learning cannot be carried out. In order to improve the ability of students, it is necessary first to improve the ability of the educators. In order to improve teacher performance, various efforts, policies and flexible strategies are needed from a leader in the school environment, namely the principal. This study aims to determine the principal's strategy in improving teacher performance during the Covid-19 pandemic at SMP Negeri 10 Binjai. The method used in this research is a qualitative research method. Data collection techniques used are interviews, observation and documentation. The results of the study show that principals carry out regular official meetings, internet training and apply open leadership strategies in improving teacher performance. The obstacles faced by the head include teachers who have not mastered technology and are not disciplined in the learning process during the pandemic